2016
DOI: 10.1038/npp.2015.371
|View full text |Cite
|
Sign up to set email alerts
|

Chemogenetic and Optogenetic Activation of Gαs Signaling in the Basolateral Amygdala Induces Acute and Social Anxiety-Like States

Abstract: Anxiety disorders are debilitating psychiatric illnesses with detrimental effects on human health. These heightened states of arousal are often in the absence of obvious threatening cues and are difficult to treat owing to a lack of understanding of the neural circuitry and cellular machinery mediating these conditions. Activation of noradrenergic circuitry in the basolateral amygdala is thought to have a role in stress, fear, and anxiety, and the specific cell and receptor types responsible is an active area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 92 publications
(120 reference statements)
3
40
0
Order By: Relevance
“…While some studies show that stress and stress-induced signaling can lead to changes in neuronal activity, other regions studied have demonstrated that neuronal activation can induce stress and anxiety-like behavior. It was recently found that optical activation of β-adrenergic receptor signaling via Gαs in BLA excitatory neurons was able to induce anxiety-like behaviors in mice (Siuda et al, 2016). These experiments show that the application of optogenetics can enable scientists to explore the effects of stressful stimuli on neuronal function but also the effects of neuronal function on behavior displays, whether in the presence of a stressful stimuli or not.…”
Section: Stress and Anxietymentioning
confidence: 99%
“…While some studies show that stress and stress-induced signaling can lead to changes in neuronal activity, other regions studied have demonstrated that neuronal activation can induce stress and anxiety-like behavior. It was recently found that optical activation of β-adrenergic receptor signaling via Gαs in BLA excitatory neurons was able to induce anxiety-like behaviors in mice (Siuda et al, 2016). These experiments show that the application of optogenetics can enable scientists to explore the effects of stressful stimuli on neuronal function but also the effects of neuronal function on behavior displays, whether in the presence of a stressful stimuli or not.…”
Section: Stress and Anxietymentioning
confidence: 99%
“…The BLA is critical for fear learning and anxiety-like behavior, but is also implicated in novelty responses (Balderston et al 2011;Jhang et al 2018). LC-NE signaling within the BLA elicits anxiety-like behavior in canonical anxiety tests as well measures of social anxiety (McCall et al 2017;Siuda et al 2016), but the role of the LC-NE à BLA circuit in neophobia has not been described.…”
Section: Ne-deficient Mice Show Reduced C-fos Induction In Select Tarmentioning
confidence: 99%
“…The full profile of Opto-β2AR signaling was recently validated as mimicry of most of the endogenous receptor’s properties. This study was also the first to express Opto-β2AR in vivo to demonstrate real time behavioral responses in endogenous neural circuits (anxiogenesis) [21**,22**]. Additionally, the first prototypes of G-protein and arrestin biased chimeras have been developed and characterized in vitro [21**].…”
Section: Opsinsmentioning
confidence: 99%
“…Each toolset has a set potential strengths and limitations, determined by experimental design. Both tools can be used complimentary to each other to dissect receptor specific from generic G-protein signaling [22**]. …”
Section: Applicability Of Optogenetic and Chemogenetic Toolsmentioning
confidence: 99%